Variation in Water Deficit and Its Association with Climate Indices in Weihe River Basin, China - Wen Liu (Atmosphere, 2024)
Based on the 24 meteorological stations in the Weihe River Basin (WRB) from 1951 to 2013, as well as the runoff data from the mainstream of the Weihe River, the temporal and spatial variations in water balance in the WRB and its relationships with runoff, the drought index, and the climate index were analyzed. The results indicate that the water balance in the WRB has been in a deficit state over the past 63 years, showing a weak declining trend with a decreasing rate of −20.04 mm/decade. Water balance is closely related to potential evapotranspiration (ET0) and precipitation (P). At the annual time scale, P plays a dominant role in water balance for 6–8 months in the WRB. The distribution of the water deficit (WD) in the WRB is uneven throughout the year, with the largest deficit occurring in June and the smallest values generally occurring in September. Furthermore, there are significant multi-scale correlations between water deficit and climate indices such as Arctic Oscillation (AO), Pacific Decadal Oscillation (PDO), and Sea Surface Temperature (SST) in the WRB. In addition, water deficit is also influenced by human activities, such as irrigation, as well as climate factors and socio-economic factors. Studying the temporal and spatial variation characteristics of water deficit and its influencing factors in the WRB is helpful toward deeply understanding the supply and demand dynamics of water resources in the basin and providing a theoretical basis and scientific guidance for the rational utilization of water resources and the high-quality development of the basin.